2023
DOI: 10.1155/2023/7484634
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Boron Nitride or Aluminum Nitride Reinforced Glass Fiber/Modified Polyphenylene Sulfide Composites

Abstract: In this work, polyphenylene sulfide (PPS) containing carboxyl group was synthesized and used to prepare PPS-2COOH/LGF/AlN and composites with high-temperature resistance, corrosion resistance, low dielectric constant, and low dielectric loss were prepared with boron nitride/aluminum nitride (BN/AlN) and glass fiber (LGF). The results showed that the introduction of carboxyl groups did not affect the structure and thermal properties of PPS. The composites exhibited good mechanical properties with a tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Table 1 shows a comparison of the dielectric properties of some different polymers. 3.0 0.03 [38,51] It was found that the most promising polymers that satisfy the initial screening step and are suitable for high energy density capacitor applications consist of at least one polar unit, -NH-, -CO-, and -O-, and at least one aromatic ring, -C 6 H 4 -and -C 6 H 2 S-.…”
Section: Selection Of Polymer Matrixmentioning
confidence: 99%
“…Table 1 shows a comparison of the dielectric properties of some different polymers. 3.0 0.03 [38,51] It was found that the most promising polymers that satisfy the initial screening step and are suitable for high energy density capacitor applications consist of at least one polar unit, -NH-, -CO-, and -O-, and at least one aromatic ring, -C 6 H 4 -and -C 6 H 2 S-.…”
Section: Selection Of Polymer Matrixmentioning
confidence: 99%